Assessment of morbidity following regional nodal dissection in the axilla and groin for metastatic melanoma. Issue 1 (21st April 2016) - Theodore, Jane E.; Frankel, Adam J.; Thomas, Janine M.; Barbour, Andrew P.; Bayley, Gerard J.; Allan, Christopher P.; Wagels, Michael; Smithers, B. Mark
Abstract : Background: This study assessed and compared the morbidity of nodal dissection in the axilla and groin including sentinel lymph node biopsy (SLNB), completion lymph node dissection for a positive SLNB (CLND) and therapeutic lymph node dissection (TLND) with and without adjuvant radiotherapy (RT). Methods: Patients who had nodal dissection in the axilla or groin for cutaneous melanoma over an 18‐year period (1995–2013) were prospectively documented on a database. The median follow‐up was nearly 3 years. Early complications and clinically relevant lymphoedema were retrospectively analysed to assess the incidence and differences between the region and type of nodal surgery. Results: Included were 1521 patients following nodal dissection in the axilla (916 patients) and groin (605 patients). Less early complications occurred following SLNB in the axilla compared with the groin (5% versus 14%, P = 0.0001). Early complications were similar for CLND and TLND in the groin (49% versus 43%, P = 0.879) and axilla (28% versus 33%, P = 0.607). Moderate to severe lymphoedema rates were similar following axillary SLNB and CLND (6% versus 8%, P = 0.407). The lymphoedema rate for groin SLNB was lower than CLND (10% versus 20%, P = 0.063). No significant difference in lymphoedema rates followed CLND and TLND in each region. Following TLND, RT increased lymphoedema rates. Conclusions: Morbidity may occur following SLNB with the groin having a higher rate of early complications and lymphoedema compared with the axilla. The morbidity following CLND and TLND were similar. Lymphoedema rates were increased following RT.